(untitled) (Journal of Partial Differential Equations, 1995)
This paper deals with the following semilinear parabolic equations with nonlinear boundary conditions u_t - Δu = f(u) - λu,x ∈ Ω, t > 0 ∂u∂n = g(u), x ∈ ∂Ω, t > 0 It is proved that every positive equilibrium solution is a threshold.